A critical examination of dietary protein requirements, benefits, and excesses in athletes - Phillips, S. M.; Moore, D. R.; Tang, J. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
There is likely no other dietary component that inspires as much debate, insofar as athletes are concerned, as protein. How much dietary protein is required, optimal, or excessive? Dietary guidelines from a variety of sources have settled on an adequate dietary protein intake for those over the age of 19 of ~0.8-0.9 g protein·kg body weight-1·d-1. According to U.S. and Canadian dietary reference intakes (33), the recommended allowance for protein of 0.8 g protein·kg-1·d-1 is "the average daily intake level that is sufficient to meet the nutrient requirement of nearly all [~98%] . . . healthy individuals" (p. 22). The panel also stated, "in view of the lack of compelling evidence to the contrary, no additional dietary protein is suggested for healthy adults undertaking resistance or endurance exercise" (33, p. 661). Currently, no group or groups of scientists involved in establishing dietary guidelines see a need for any statement that athletes or people engaging in regular physical activity require more protein than their sedentary counterparts. Popular magazines, numerous Web sites, trainers, and many athletes decry protein intakes even close to those recommended. Even joint position stands from policy-setting groups state that "protein recommendations for endurance athletes are 1.2 to 1.4 g/kg body weight per day, whereas those for resistance and strength-trained athletes may be as high as 1.6 to 1.7 g/kg body weight per day" (1, p. 1544). The divide between those setting dietary protein requirements and those who might be making practical recommendations for athletes appears substantial, but ultimately, most athletes indicate that they consume protein at levels beyond even the highest recommendations. Thus, one might conclude that any debate on protein "requirements" for athletes is inconsequential; however, a critical analysis of existing and new data reveals novel ideas and concepts that may represent some common ground between these apparently conflicted groups. The goal of this review was to provide a critical and thorough analysis of current data on protein requirements in an attempt to provide some guidance to athletes, trainers, coaches, and sport dietitians on athletes' protein intake. In addition, an effort was made to clearly distinguish between "required" dietary protein, "optimal" intakes, and intakes that are likely "excessive," perhaps not from the standpoint of health, but certainly from the standpoint of potentially compromised performance.